A Culinary Dose of Herbs and Spices Improves 24-Hour Blood Pressure in Adults at Risk for Cardiometabolic Diseases: A Randomized, Crossover, Controlled-Feeding Study. (7th June 2021) - Petersen, Kristina; Davis, Kristin; Rogers, Connie; Proctor, David; West, Sheila; Kris-Etherton, Penny
Abstract: Objectives: Intake of a herb/spice containing meal attenuates post-prandial lipemia, hyperglycemia and oxidative stress, and improves endothelial function. No randomized controlled trials have examined the cardiometabolic effects of longer-term intake of mixed herbs and spices. We aimed to assess the effect of an average American diet containing herbs and spices at 0.5 (Low Spice Diet; LSD), 3.3 (Moderate Spice Diet; MSD) and 6.6 (High Spice Diet; HSD) g/day/2100 kcal on lipids/lipoproteins as well as other risk factors for cardiometabolic diseases in at-risk adults. Methods: A three-period, randomized, crossover, controlled-feeding study including 71 participants (55% female; 44 ± 11 years, BMI 29.7 ± 2.9 kg/m 2 ; waist circumference 102.4 ± 7.3 cm) was conducted. Each diet was provided for 4-weeks with a minimum 2-week wash-out period. Outcomes were assessed at baseline and the end of each diet period. On 2 separate days at each time point a fasting blood draw was taken for analysis of lipids/lipoproteins, glucose and insulin. A SphygmoCor XCEL was used for pulse wave analysis and pulse wave velocity assessment, and participants wore an ambulatory blood pressure monitor for a 24-hour period. Results: No between-diet effects were observed for LDL-cholesterol, the primary outcome. Between-diet differences were observed for mean 24-hour systolic ( P < 0.001) and diastolic ( P < 0.001) blood pressure. The HSD lowered mean 24-hour systolic and diastolic blood pressure compared to the MSD (−2.2 mmHg; 95% CI −0.7, −3.8; P = 0.002 and −1.6 mmHg; 95% CI −0.6, −2.5; P < 0.001, respectively) and LSD (−2.1 mmHg; 95% CI −3.6, −0.6; P = 0.004 and −1.7 mmHg; 95% CI −0.7, −2.7; P < 0.001, respectively); no differences were detected between the LSD and MSD. No between-diet effects were observed for clinic measured blood pressure, markers of glycemia, or vascular function. Conclusions: In the context of a suboptimal U.S. style diet, addition of a culinary dose of mixed herbs and spices (6.6 g/day/2100kcal) improved 24-hour blood pressure after 4-weeks, compared to lower doses (0.5 and 3.3 g/day/2100 kcal), in adults at elevated risk for cardiometabolic diseases. Funding Sources: McCormick Science Institute and the National Center for Advancing Translational Sciences, National Institutes of Health (1UL1TR002014–01).